(Factors Affecting the Selection of the Saudi Consumer for Commercial Centers in Najran City (Saudi Arabia - Mohamed, Mohamed El Amin Mahmoud; El Ali, Rami Osama (Journal of Economic, Administrative and Legal Sciences, 2017)
This study aimed to identify factors that affecting on Saudi consumer choice for shopping malls in Najran city. The study problem was determining those factors that drive Saudi consumer to shopping in those malls. The Statistical hypotheses that examined the impact of the following factors on consumer choice to shopping malls in najran were formulated: mall environment, the products offered at the mall, the price, the promotion, the location of the mall, mall employees, the family atmosphere and entertainment. To get the results, this study used descriptive analytical approach according to primary data that collected through questionnaire tool and secondary data that collected from books and scientific articles related to the subject. The study reached that there is significant statistical impact of the following variables: mall environment, verity of products, products prices. Promotion, mall place, mall employee’s services, and family atmosphere and entertainments on consumer choice to shopping malls in Najran. The more important recommendations of the study are the shopping malls must pay attention to provide some entertainment for customers of all ages with a view to attract them to the shopping malls.